Teacher's Perception of Students' Silence in EFL Classroom Context: A Case Study - Della Putri Kandilla; Nita Sari Narulita Dewi; Ratu Sarah Pujasari (Siliwangi University, 2021)
Numerous studies have investigated the phenomenon of students’ silence in the EFL classroom context. However, they are less attention in documenting the emergence of the teacher’s perception. Therefore, the present research aimed to dig the teacher’s perception and also seek the solution or teaching strategies that can be applied for encouraging silent students in the learning. The research is a case study and the data collection is using qualitative design through a semi-structured interview which involves a female teacher who has taught for about 30 years in one secondary school in Tasikmalaya. The data is analyzed thematically and the results showed that the teacher perceived the phenomenon of students’ silence into psychological aspects, students’ low self-motivation, and low self-confidence in language learning. The present research revealed that teacher’s perception influences all of the actions that applied in the classroom. The contributions are also viewed from the present study. They are teaching strategies such as integrated game-based learning (GBL), incorporated role-play, group presentation, and built a positive teacher-student relationship, and conducted external encouragement like appreciation. Those can be practiced by the teacher, novice teacher, or student-teacher particularly in dealing with the phenomenon of students’ silence itself.